The year of social sciences and humanities - Aguillo, Isidro F. (Anuario ThinkEPI, 2012)
Library & Information science in Spain is currently facing serious problems because the divorce between the academic and the professional approach, being the first closer to the integration in the humanities and social sciences and the second with a more technological profile. The unfortunate proposal for a specific and differential treatment of the social sciences and humanities in the evaluation processes is going to penalize severely to our discipline and urgent and serious measures should be taken for avoiding a catastrophic situation. These measures include, among others, the pursuit of excellence, punishing the scientific fraud and plagiarism, and defending not only the publication but also the reading in English. An even stronger support of open access initiatives is a sound objective, including the adoption of new standards, such as for example the not well-known yet strategies of the new Book citation index. Today the professional profile should be more involved in the generation of content than in t its mere labeling, especially taking control of the usage statistics and indicators.